New constraints on the Hadean to Proterozoic history of the Jack Hills belt, Western Australia - Wang, Q.; Wilde, Simon (Elsevier BV, 2018)
© 2017 International Association for Gondwana Research A 1010 m traverse line on the eastern flank of Eranondoo Hill was mapped and sampled in detail, crossing the entire width of the Jack Hills supracrustal belt, Western Australia. The facies associations indicate a northward deepening of the sedimentary sequence and confirm a fan delta depositional environment. From a total of 157 samples processed for zircon extraction, precise MC-ICP-MS and SHRIMP zircon U-Pb isotope results from 51 of these yielded a total of 6308 dates that included 2819 concordant ages ranging from 4381 ± 10 Ma to 1618 ± 22 Ma (2s). The rocks that yielded Proterozoic ages include schist, sandstone, quartzite and matrix-supported conglomerate and are widely distributed across the belt. However, there are similar lithologies that yield only Archean ages and so there is no relationship between rock-type and depositional age. Overall, rocks proven to contain Proterozoic zircon make up only ~ 12% of the belt, but confirm the presence of both Archean and Proterozoic successions at Jack Hills. A total of 1093 of the most concordant zircon grains from 46 samples were analysed for Lu-Hf, with negative e Hf(t) values making up 94.3% of the population. For the Proterozoic zircons, the e Hf(t) values ranged from - 22.1 to 1.0, with an average e Hf(t) value of - 8.4 (n = 10). For zircons with U-Pb ages from 2.5 to 3.0 Ga, the e Hf(t) values ranged from - 14.7 to - 1.6, with an average value of - 7.9 (n = 25). Zircons with U-Pb ages that ranged from 3.0 Ga to 4.0 Ga, have e Hf(t) values from - 17.6 to 5.6, with an average e Hf(t) value of - 6.3 (n = 873). For Hadean zircons, the e Hf(t) values ranged from - 11.0 to 5.6, with an average e Hf(t) value of - 3.4 (n = 185). Importantly, 92% of the Hadean zircon population recorded negative e Hf(t) values, with Hf model ages indicating initial crustal generation at 4.4–4.5 Ga. The Hf isotope data do not favour significant juvenile input into the parental Hadean magmas. Instead, the data support extensive reworking of long-lived, mafic, intermediate and felsic Hadean crust, which could only endure at or near the Earth's surface in the absence of subduction, thus mitigating against Hadean plate tectonics.